The Science of "Muddling Through" - Lindblom, Charles E. (Public Administration Review, 1959)
Short courses, books, and articles exhort administrators to make decisions more methodically, but there has been little analysis of the decision-making process now used by public administrators. The usual process is investigated here-and generally defended against proposals for more "scientific" methods. Decisions of individual administrators, of course, must be integrated with decisions of others to form the mosaic of public policy. This integration of individual decisions has become the major concern of organization theory, and the way individuals make decisions necessarily affects the way those decisions are best meshed with others'. In addition, decision-making method relates to allocation of decision-making responsibility-who should make what decision. More "scientific" decision-making also is discussed in this issue: "Tools for Decision-Making in Resources Planning."

Requisite Variety and Its Implications for the Control of Complex Systems - Ashby, W. Ross (Cybernetica, 1958)